(untitled) (Semiárida, 2020)
Four diets for growing pigs based on grain sorghums with different tannin levels were approved: High (T3), medium (T2), low (T1), and a very low one as a control (T0). Diets were isonitrogenous (16%GP) and isoenergetic (13,8 MJ/kg) ones; they were valued in four replicate animals received each diet using a randomized design, with one pig DxHxLW, in metabolism cages. No significative differences were found (p> 0,05) for daily gain and daily feed intake on treatments, observing an unfavorable slight biological difference on T3 on feed gain (control: 2.7:1 vs. T1: 2,8:1, T2: 2,8:1 and T3: 3,0:1). The largest energy loss was on the feces and relatively slight on urine. The energetic maintenance cost significatively favorable (p<0,05) for the control 12,81 MJ/kg0,75 vs. T1: 14,77; T2: 15,73; and T3: 14,33. GP to DP convertion was less efficient on treatments with high tannin content, indicating that tannins act immediately at digestive tract inhibiting part of protein metabolism. Nitrogenous and energy’s efficiency was obtained due to differences that exist owing to the digestive metabolism. It was measured taking into account the protein wasted away and retained and the metabolic coefficient. No significate differences were found on the digestibility values of different diets. The energy cost to produce fat was favorable for tannin treatments (4,56 MJ/kg0,75 for the sample vs, T1: 3,76; T2: 2,63; and T3: 4,52) values similar to muscle production (4,35 MJ/kg0,75 for the sample vs. T1: 4,43; T2: 4,64 and T3: 3,84), but corporal composition resulted to be inferior for fat production. The indirect spectrometric method was successful in time and drug saving and for the analysis of tannin with "catequina" as a chemical base which is the real antimetabolic factor, compared to Folin Denis method which is very slow and determines all the polyphenol composed in the sample expressing in equivalent percentage of tannin acid, giving an incorrect value.